Implementing Digital Parental involvement in language learning; an action research study using ClassTag - Christodoulidou Michael, Chrysoula (Language Center, Cyprus University of Technology, 2020)
During this study, research was designed to offer insights regarding best-practice methods of parent/teacher communication in the classroom using an application, Classtag. This comparative action research study was conducted in Limassol, Cyprus and the actual implementation procedure took place both in a private language institute and at the student’s home. The study consisted of a sample size of 11 students at A1 level according to the Common European Framework (CEFR) and their parents. For the needs of the study, Classtag was used to build a useful communication channel that would benefit a student’s language education. The findings showed that the language teacher had the ability to introduce and redesign this particular tool in order to match the needs of this particular group of language students and parents and have positive results in the process of language learning. The results indicated that the parents in this classroom generally perceived their involvement positively and were willing to support their children in learning the foreign language using Classtag. The findings also showed positive attitudes to this effort both from parents and the students and gave rise to substantial beliefs on behalf of the parents on how this application could be further used for maximizing language learning success. The relationship between the participants was positively affected as well. This current study extends Keye’s (2000) seminal work, where she identified communication as the central aspect of Epstein’s (1983;1995) typology of parent involvement. Implications of the findings and recommendations for further research are discussed herein.
Keywords: Classtag; Application; Parent/teacher communication